Preservice Esl Teachers’ Beliefs About Learning Arabic - Zailani, Jusoh (2017)
This paper is written to investigate the beliefs of student teachers majoring in English about learning Arabic as a foreign language. This paper presents the results from a larger study of four languages, one of which is Arabic. The respondents of this study were students in diploma in TESL programme at a higher education institution in Malaysia who were enrolled in Arabic as foreign language to meet the graduation requirement. Data for the study were collected using BALLI, an instrument to measure students’ beliefs about language learning. As this is a descriptive study, the data gathered were analysed using percentage. In general, respondents held positive beliefs in learning Arabic. The findings have a number of contributions. One important pedagogical implication the study contributes is with regards to the needs to inculcate realistic beliefs among students in learning Arabic as a foreign language.